Publication of scientific research presented at scientific meetings of the British Association of Oral and Maxillofacial Surgeons: 10 years on – have we published or perished?. Issue 7 (September 2018) - Watson, L.; Reed, A.; Jakharia-Shah, N.; Brennan, P.A.; Hammond, D.; Collier, J.
Abstract: In 2009 we evaluated the publication of research presented at annual scientific meetings of the British Association of Oral and Maxillofacial Surgeons (BAOMS) 2002–2006, inclusive. Since then, the format of these meetings has changed, there has been a rapid increase in the number of online-only journals, and restraints on time during training and consultant practice have continued. We have therefore investigated the pattern of publication after presentation at these meetings between 2010 and 2014. All abstracts accepted for oral presentations or posters were included, and publication had to follow no more than four years later. We searched PubMed for papers in peer-reviewed journals and compared the data with those from 2002–2006. A total of 975 abstracts were accepted (2010–2014) of which 221 (23%) went on to be published. The median (IQR) delay to publication was 13 (4–25) months. Most were clinical papers from groups based in the UK (p < 0.001) and most were published in BJOMS (p < 0.001). The rate of publication has not changed significantly between the two periods (23% compared with 24%), and patterns in the type of papers, delays, journals, and research groups, were similar. Despite consistent rates of publication within the specialty, OMFS produces fewer publications after presentation than other surgical specialties. Further research is required to evaluate this more fully.